THE APPLICATION OF CONSTRAINT-INDUCED MOVEMENT THERAPY IN IMPROVING LOWER EXTREMITY FUNCTIONAL ABILITY IN POST-STROKE PATIENTS: A CRITICAL REVIEW - Rifai, Ahmad; Amalina, Fildzah; Atikasari, Dewi Ayu; Nisa, Salma Fadila; Anggraeni, Fitria Rizky; Mahdiyah, Rahadyani Ridha; Pristianto, Arif (JTH: Journal of Technology and Health, 2025)
Stroke is a disease that affects the arteries in the brain, often caused by a blood clot that blocks blood flow, disrupting the delivery of oxygen and nutrients to brain tissue. One of the common consequences in stroke patients is movement impairment, particularly walking difficulties due to muscle weakness and balance disorders. This study aims to evaluate the effectiveness of Constraint-Induced Movement Therapy (CIMT) compared to conventional therapy in improving lower extremity functional ability in post-stroke patients. The method used is a literature review with meta-analysis from seven studies obtained through a PICO-based search on PubMed and Google Scholar databases. The meta-analysis results showed that patients undergoing CIMT experienced significantly greater improvement in functional ability than those receiving conventional therapy (SMD = 0.74; 95% CI = 0.39 to 1.09; p < 0.00001). However, the high heterogeneity (I² = 96%) indicates substantial variability among studies in terms of design, population, and interventions. Therefore, the findings should be interpreted with caution and highlight the need for further research with more standardized designs.